Graphynes: an alternative lightweight solution for shock protection - Xia, Kang; Zhan, Haifei; Ji, Aimin; Shao, Jianli; Gu, Yuantong; Li, Zhiyong (Beilstein Journal of Nanotechnology, 2019)
The excellent mechanical properties of graphyne (GY) have made it an appealing candidate in the field of impact protection. We assessed the deformation mechanisms of monolayer GY nanosheets of different morphologies, including α-GY, β-GY, γ-GY and 6612-GY, under supersonic-velocity impacts (from 1 to 6 km/s) based on in silico studies. Generally, cracks initiate at the geometry center and the nanosheet experiences significant out-of-plane deformation before the propagation of cracks. Tracking the atomic von Mises stress distribution, it is found that its cumulative density function has a strong correlation with the magnitude of the Young’s modulus of the GYs. For nanosheets with a higher Young’s modulus, it tends to transfer momentum at a faster rate. Thus, a better energy dissipation or delocalization is expected during impact. This study provides a fundamental understanding of the deformation and penetration mechanisms of monolayer GY nanosheets under impact, which is crucial in order to facilitate their emerging applications for impact protection.
Keywords: graphyne; in silico studies; stress wave propagation; supersonic-velocity impact

(untitled) - Diederich, F. (Nature, 1994)

(untitled) - Zhang, Y. Y.; Pei, Q. X.; Wang, C. M. (Appl. Phys. Lett., 2012)

(untitled) - Tahara, K.; Yamamoto, Y.; Gross, D. E.; Kozuma, H.; Arikuma, Y.; Ohta, K.; Koizumi, Y.; Gao, Y.; Shimizu, Y.; Seki, S.; Kamada, K.; Moore, J. S.; et al. (Chem. – Eur. J., 2013)

(untitled) - Kehoe, J. M.; Kiley, J. H.; English, J. J.; Johnson, C. A.; Petersen, R. C.; Haley, M. M. (Org. Lett., 2000)

(untitled) - Li, Q.; Li, Y.; Chen, Y.; Wu, L.; Yang, C.; Cui, X. (Carbon, 2018)

(untitled) - Li, J.; Xie, Z.; Xiong, Y.; Li, Z.; Huang, Q.; Zhang, S.; Zhou, J.; Liu, R.; Gao, X.; Chen, C.; Tong, L.; Zhang, J.; et al. (Adv. Mater. (Weinheim, Ger.), 2017)

(untitled) - Yuan, Q.; Ding, F. (Nanoscale, 2014)

(untitled) - Kou, J.; Zhou, X.; Lu, H.; Wu, F.; Fan, J. (Nanoscale, 2014)

(untitled) - Peng, Q.; Dearden, A.; Crean, J.; Han, L.; Liu, S.; Wen, X.; De, S. (Nanotechnol., Sci. Appl., 2014)

(untitled) - Rai, D. K.; Chakraborty, H.; Shukla, A. (J. Phys. Chem. C, 2018)

(untitled) - Zhang, Q.; Tang, C.; Zhu, W.; Cheng, C. (J. Phys. Chem. C, 2018)

(untitled) - Pokropivny, V. V.; Ivanovskii, A. L. (Russ. Chem. Rev., 2008)

(untitled) - Li, G.; Li, Y.; Liu, H.; Guo, Y.; Li, Y.; Zhu, D. (Chem. Commun., 2010)

(untitled) - Enyashin, A. N.; Ivanovskii, A. L. (Phys. Status Solidi B, 2011)

(untitled) - Cranford, S. W.; Buehler, M. J. (Carbon, 2011)

(untitled) - Yang, Y.; Xu, X. (Comput. Mater. Sci., 2012)

(untitled) - Peng, Q.; Ji, W.; De, S. (Phys. Chem. Chem. Phys., 2012)

(untitled) - Kutty, S. K. N.; Nando, G. B. (J. Appl. Polym. Sci., 1992)

(untitled) - Auerbach, I. (J. Appl. Polym. Sci., 1989)

(untitled) - Panich, S.; Uthaisangsuk, V.; Suranuntchai, S.; Jirathearanat, S. (Mater. Sci. Eng., A, 2014)

(untitled) - Govindaraj, N. V.; Lauvdal, S.; Holmedal, B. (J. Mater. Process. Technol., 2013)

(untitled) - Liou, J.-C.; Johnson, N. L. (Science, 2006)

(untitled) - Chuvilin, A.; Meyer, J. C.; Algara-Siller, G.; Kaiser, U. (New J. Phys., 2009)

(untitled) - Jin, C.; Lan, H.; Peng, L.; Suenaga, K.; Iijima, S. (Phys. Rev. Lett., 2009)

(untitled) - Kotakoski, J.; Santos-Cottin, D.; Krasheninnikov, A. V. (ACS Nano, 2012)

(untitled) - Lee, J.-H.; Loya, P. E.; Lou, J.; Thomas, E. L. (Science, 2014)

(untitled) - Haque, B. Z. (Gama).; Chowdhury, S. C.; Gillespie, J. W., Jr (Carbon, 2016)

(untitled) - Yoon, K.; Ostadhossein, A.; van Duin, A. C. T. (Carbon, 2016)

(untitled) - Xia, K.; Zhan, H.; Hu, D.; Gu, Y. (Sci. Rep., 2016)

(untitled) - Plimpton, S. (J. Comput. Phys., 1995)

(untitled) - Yin, H.; Qi, H. J.; Fan, F.; Zhu, T.; Wang, B.; Wei, Y. (Nano Lett., 2015)

(untitled) - Hernandez, S. A.; Fonseca, A. F. (Diamond Relat. Mater., 2017)

(untitled) - Brenner, D. W.; Shenderova, O. A.; Harrison, J. A.; Stuart, S. J.; Ni, B.; Sinnott, S. B. (J. Phys.: Condens. Matter, 2002)

(untitled) - Stuart, S. J.; Tutein, A. B.; Harrison, J. A. (J. Chem. Phys., 2000)

(untitled) - Sha, Z. D.; Pei, Q. X.; Liu, Z. S.; Shenoy, V. B.; Zhang, Y. W. (Carbon, 2014)

(untitled) - Sha, Z. D.; Wan, Q.; Pei, Q. X.; Quek, S. S.; Liu, Z. S.; Zhang, Y. W.; Shenoy, V. B. (Sci. Rep., 2014)

(untitled) - Sha, Z. D.; Branicio, P. S.; Pei, Q. X.; Sorkin, V.; Zhang, Y. W. (Comput. Mater. Sci., 2013)

(untitled) - Mylvaganam, K.; Zhang, L. C. (Nanotechnology, 2007)

(untitled) - Hoover, W. G. (Phys. Rev. A, 1985)

(untitled) - Verlet, L. (Phys. Rev., 1967)

(untitled) - Diao, J.; Gall, K.; Dunn, M. L. (J. Mech. Phys. Solids, 2004)